The Effect of Electrode Types and Voltage on COD in Flavoring Industry Waste Using Electrocoagulation - Muhammad Faishal Muzakky; Ilma Fadlilah; Rosita Dwityaningsih (Stannum : Jurnal Sains dan Terapan Kimia, 2023)
Industrial waste is something that must be managed by every company so as not to endanger the surrounding environment. One of the industries that must process its waste is the food flavoring industry. This industrial waste has the characteristics of high Chemical Oxygen Demand (COD) and Total Suspended Solid (TSS) values. This study used the electrocoagulation method which aims to treat this food flavor industrial waste. This electrocoagulation method uses variations of aluminum and steel electrodes, variations of voltaje 6v, 9v and 12v where the waste will be processed for 120 minutes. The results of this study were the COD value to 31.25 Mg/l from the initial 22,310 mg/L.